Simultaneous Spectrophotometric Determination of Paracetamol, Propyphenazone and Caffeine By Using Absorption Ratio Method - Pulungan, Ainil Fithri; DLP., Effendy; MS., Siti (Asian Journal of Pharmaceutical Research and Development, 2018)
The Absorption Ratio method involves measuring the absorbance at two wavelengths, namely the iso-absorptive point and the maximum wavelength. Its method could be an option in determining the level of a drug. The aim of this study was to determine whether the absorption ratio method can be used to determine the levels of paracetamol (PCT), propyphenazone (PRO) and caffeine (CAF) in tablet form. The absorption ratio method was used to determine the levels of the mixed drug compound without the separation stage and using the maximum wavelength and iso-absorptif point. The result of the study showed that the absorption ratio method used to solve multicomponent problems in tablet form can be performed and satisfy the validation requirements of the method according to international Conference on Harmonization Q2 (R1) (ICH) guidelines. The absorption ratio method was a simple and accurate to be used determine PCT, PRO, CAF in tablet form. Keywords : Paracetamol, propyphenazone, caffeine, absorption ratio